Dynamics of the island mass effect – Part 1: Detecting the extent - G. Bourdin; L. Karp-Boss; L. Karp-Boss; F. Lombard; G. Gorsky; E. Boss (Biogeosciences)
In the vast Pacific Ocean, remote islands and atolls induce mesoscale and sub-mesoscale processes that significantly impact the surrounding oligotrophic ocean, collectively referred to as the island mass effect (IME). These processes include nutrient upwelling and phytoplankton biomass enhancement around islands, creating spatial and temporal heterogeneity in biogeochemical properties. Previous algorithms developed for detecting the IME using satellite data are based on monthly or longer averages of satellite-derived chlorophyll a concentrations. As such, they tend to underestimate the true extent of this phenomenon because they do not take into account sub-mesoscale and short-term temporal variations and because of the sensitivity of the detection algorithm to single-pixel variability. Here we present a new approach that enhances satellite data recovery by merging products from multiple sensors and applying the POLYMER atmospheric correction. By integrating modeled surface currents with higher-temporal-resolution satellite observations, we dynamically track chlorophyll a enhancements associated with the IME and the advection of detached patches and filaments over distances exceeding 1000 km from their source. Our findings, applied to four island groups in the South Pacific, suggest that the ecological influence of the IME on the oligotrophic ocean is much larger than previously recognized. This work provides a foundation for improved mechanistic understanding of the IME and suggests broader implications for ocean ecology in subtropical regions. The approach developed here could also be applied in studies on biological responses to other mesoscale and sub-mesoscale processes in other parts of the world's oceans.